2005
DOI: 10.1614/wt-04-121r2
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn Hybrid Sensitivity to Clopyralid

Abstract: Limited information exists on sweet corn tolerance to postemergence (POST) applications of clopyralid under Ontario growing conditions. Eight sweet corn hybrids were evaluated for tolerance to clopyralid in three field experiments conducted in 2001 and 2002 in Ontario. Clopyralid was applied POST at 200 and 400 g ai/ha, the proposed and twice the proposed registered rate for use in sweet corn in Ontario. Sweet corn response to clopyralid did not vary among the hybrids tested. In 2001, visual injury among hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(5 reference statements)
5
2
0
Order By: Relevance
“…However, none of the injury caused lasting damage and was not statistically significant. Visible injury did not increase significantly as herbicide rate increased and is consistent with previous studies on clopyralid (Soltani et al, 2005a) and topramezone (Soltani et al, 2007). This observation is in contrast to that observed when sensitive sweet corn hybrids were treated with bentazon (Diebold et al, 2004), isoxaflutole , mesotrione applied POST , nicosulfuron (Morton and Harvey, 1992;O'Sullivan et al, 2000), nicosulfuron plus rimsulfuron (O'Sullivan et al, 1995;O'Sullivan and Bouw, 1998), primisulfuron (O'Sullivan and Sikkema, 2002), prosulfuron (O'Sullivan and Sikkema, 2001), or thifensulfuron-methyl (Soltani et al, 2005b) in which injury increased with increasing herbicide rate.…”
Section: Resultssupporting
confidence: 92%
“…However, none of the injury caused lasting damage and was not statistically significant. Visible injury did not increase significantly as herbicide rate increased and is consistent with previous studies on clopyralid (Soltani et al, 2005a) and topramezone (Soltani et al, 2007). This observation is in contrast to that observed when sensitive sweet corn hybrids were treated with bentazon (Diebold et al, 2004), isoxaflutole , mesotrione applied POST , nicosulfuron (Morton and Harvey, 1992;O'Sullivan et al, 2000), nicosulfuron plus rimsulfuron (O'Sullivan et al, 1995;O'Sullivan and Bouw, 1998), primisulfuron (O'Sullivan and Sikkema, 2002), prosulfuron (O'Sullivan and Sikkema, 2001), or thifensulfuron-methyl (Soltani et al, 2005b) in which injury increased with increasing herbicide rate.…”
Section: Resultssupporting
confidence: 92%
“…ha -1 . Little visible injury seen in different sweet maize varieties evaluated in this study is similar with previous studies on clopyralid [21] and to a Abbreviations: su = sugary; sh 2 = shrunken endosperm mutant genotype; b Results are averaged for both locations and years; means followed by the same letter within a row for each treatment are not significantly different according to Fisher's Protected LSD test (P ≤ 0.05).…”
Section: Crop Injurysupporting
confidence: 89%
“…ha -1 . Lack of any height reduction between sweet maize hybrids evaluated in this study with saflufenacil and saflufenacil plus dimethenamid-p is similar to those found with other herbicides such as clopyralid, halosulfuron and topramezone [21,26].…”
Section: Plant Heightsupporting
confidence: 79%
See 2 more Smart Citations